Investment Analysis of Excavator in Sand Mining on the Slopes of Mount Merapi - Saputro, Cahyo Dita; Rizal Setiawan; Dwi Kurniati (Marasofi International Media and Publishing (MIMP), 2025)
The definition of mining and quarrying is constructed as an activity that includes research, management, and exploitation. Sand mining is part of non-metal mining business activities that aim to produce its associated minerals. This study aims to determine the results of the evaluation of the feasibility of heavy equipment investment in Excavators based on calculations using the NPV (Net Present Value), IRR (Internal Rate of Return), BEP (Break Event Point) and PP (Payback Period). This research was conducted surveys, observations and interviews to obtain data. The results of this study Investment in the procurement of heavy equipment Excavator is feasible to run because the Net Present Value (NPV) value is positive (+) which means it is good and acceptable while the resulting NPV value is Rp1,944,640,086.47. Then analyze the calculation of the feasibility of the Internal Rate of Return (IRR) obtained 26%. Thus IRR> MARR = 26%> 15.5% or according to the calculation of IRR this investment is RIGHT to run. Furthermore, from the analysis of the calculation of the Break Even Point (BEP), the calculation results obtained are 5.2153 years or BEP occurs when the break-even point occurs when PM - PK = Rp 5.006.705.873. In the Payback Period (PP) research, the investment turning point occurred in year 5.6856 at a value of Rp 4.009.690.743,31. It can be interpreted that for investment within a period of 10 years is FAIR.